Rural Schools and the Policy-Practice Gap: Teachers’ Struggles with Differentiated Instruction in Eastern Indonesia - Niaty Beladinna; Muamaroh, Muamaroh; Muamaroh, Endang Fauziati (International Journal of Educational Technology and Society, 2025)
This study investigates teachers’ perceptions, challenges, and institutional support related to the implementation of Differentiated Instruction (DI) in a rural Indonesian secondary school under the context of the Kurikulum Merdeka reform. While DI is widely recognized as a student-centered pedagogical framework that adapts content, process, product, and learning environment to students’ readiness, interests, and learning profiles (Tomlinson, 2017), its application in rural contexts remains underexplored. Employing a qualitative case study design, data were collected from three English teachers and two school stakeholders at MTs N 2 Manggarai Barat through semi-structured interviews, questionnaires, and classroom observations. Thematic analysis revealed that teachers perceived DI as a way to recognize learner diversity and as part of curriculum compliance, but their practices often remained partial and uneven. Stakeholders expressed awareness of DI, though with differing emphases: the headmaster focused on inclusivity, while the curriculum coordinator referred to multiple intelligences and student potential. Teachers faced challenges in three main areas: managing student diversity and curriculum shifts, preparing the Modul Ajar, and addressing students’ limited English vocabulary. Institutional support was evident through facilities, monitoring, and professional development, yet remained largely administrative rather than pedagogical. These findings confirm earlier studies that DI in Indonesia is conceptually valued but practically constrained by systemic, contextual, and linguistic barriers. The study recommends sustained, hands-on professional development, leadership mentoring, and reduced administrative burdens to enable DI’s transformative potential in rural schools.